Integrator complex collapse: A mechanistic route to integrated stress response and disease - Valtorta, Beatrice; Hanzlikova, Hana (Molecular cell, 2025)
In a recent Cell article, Baluapuri et al.1 show that loss of the Integrator (INT) complex activates the integrated stress response via double-stranded RNA from incomplete pre-mRNAs, revealing a link to INT-related neurodevelopmental diseases and potential therapeutic targets.
Keywords: Stress, Physiological; dvouvláknová RNA; Neurodevelopmental Disorders; zvířata; Humans; fyziologický stres; neurovývojové poruchy; RNA, Double-Stranded; lidé; Animals